Light-Induced Reactions within Poly(4-vinyl pyridine)/Pyridine Gels: The 1,6-Polyazaacetylene Oligomers Formation - Evgenia Vaganova (MDPI AG, 2021)
Cyclic 6-membered aromatic compounds such as benzene and azabenzenes (pyridine, pyridazine, and pyrazine) are known to be light-sensitive, affording, in particular, the Dewar benzene type of intermediates. Pyridine is known to provide the only Dewar pyridine intermediate that undergoes reversible ring-opening. We found that irradiation of photosensitive gels prepared from poly(4-vinyl pyridine) and pyridine at 254 or 312 nm leads to pyridine ring-opening and subsequent formation of 5-amino-2,4-pentadienals. We show that this light-induced process is only partially reversible, and that the photogenerated aminoaldehyde and aminoaldehyde-pending groups undergo self-condensation to produce cross-linked, conjugated oligomers that absorb light in the visible spectrum up to the near-infrared range. Such a sequence of chemical reactions results in the formation of gel with two distinct morphologies: spheres and fiber-like matrices. To gain deeper insight into this process, we prepared poly(4-vinyl pyridine) with low molecular weight (about 2000 g/mol) and monitored the respective changes in absorption, fluorescence, 1H-NMR spectra, and electrical conductivity. The conductivity of the polymer gel upon irradiation changes from ionic to electronic, indicative of a conjugated molecular wire behavior. Quantum mechanical calculations confirmed the feasibility of the proposed polycondensation process. This new polyacetylene analog has potential in thermal energy-harvesting and sensor applications.